On the use of proper generalized decompositions for solving the multidimensional chemical master equation - Chinesta, Francisco; Ammar, Amine; Cueto, Elías (European Journal of Computational Mechanics, 2010)
In this paper we review the possibilities associated with the use of Proper Generalized Decompositions for solving models established in highly multidimensional spaces. This technique has also been recently extended to problems that can be, under some circumstances, seen as multidimensional.